The Need for Specialized Pediatric Cardiac Critical Care Training Program in Limited Resource Settings - Murni, Indah K.; Musa, Ndidiamaka L. (Frontiers in Pediatrics, 2018)
Congenital heart disease (CHD) is one of major global health problems with the highest birth prevalence are in low- and middle-income countries. In these populous countries, basic health services for children with congenital heart disease, including surgery, are lacking. Even though surgery is performed, outcome after cardiac surgery is influenced by the quality of the postoperative management and a high morbidity and mortality is reported. Therefore, there is an urgent need for comprehensive interventions to provide high quality cardiac intensive care programs and to improve the quality of pediatric cardiac surgery services in order to address morbidity and mortality after cardiac surgery. The development and training of the health workers in the field of pediatric cardiac intensive care program is required and these should be conducted earlier before the actual implementation of the program in limited resources settings.